KATEGORISASI EMOSI TOKOH UTAMA “NICKY” DALAM WINTER DREAMS KARYA MAGGIE TIOJAKIN: KAJIAN PSIKOLOGI SASTRA - Rahmah Purwahida (p-ISSN 2356-0576, 2020)
Abstract: The purpose of this study is to describe the emotional categorization of the main character in the novel Winter Dreams by Maggie Tiojakin based on David Krech's theory of emotional categorization with a literary psychology approach. The research method used is descriptive qualitative content analysis techniques. The validity and reliability of the data were obtained by semantic validity and triangulation with experts. The results of this study describe the findings of David Krech's emotional categorization of the main character "Nicky. David Krech's theory of emotional categorization as an appropriate theoretical basis for dissecting the emotional categorization of the main character "Nicky" in this novel. Some show the findings of emotions that are interrelated with one another. This shows that the emotional classification that has been detailed by Krech is proven through novel quotations so that this research confirms the existence of Krech's truth about emotions.Keywords: main character emotions, David Krech, Winter Dreams, Maggie Tiojakin, psychology of literature